Empowering Adolescent Girls Through Social Organisation-Based Mentoring to Prevent Malnutrition - Nur Khafidhoh; S.A. Nugraheni; Ayun Sriatmi; Sri Winarni (Journal of Public Health and Pharmacy, 2025)
Introduction: Adolescent girls are prone to nutrition-related problems, ranging from anaemia, SEZ, undernutrition and overnutrition. Currently, more interventions are conducted on school-aged adolescents, while adolescents who are no longer in school have not been addressed. Implementation of interventions in the community, such as youth organisations and religious organisations, not only in schools. This can increase accessibility and participation among adolescents who are not in formal education young women-based social organisations can be involved in interventions to prevent adolescent malnutrition through a mentoring model. The aim of this study was to analyse the effect of organisation-based mentoring on improving knowledge, this study aims to analyse the differences in knowledge, practice of malnutrition prevention in the form of measurement of calorie adequacy and iron intake.